Deciphering the associations between soil microbial diversity and ecosystem multifunctionality driven by long‐term fertilization management. (11th January 2018) - Luo, Gongwen; Rensing, Christopher; Chen, Huan; Liu, Manqiang; Wang, Min; Guo, Shiwei; Ling, Ning; Shen, Qirong
Abstract: An increasing number of studies indicate that microbial diversity plays a crucial role in the mediation of ecosystem multifunctionality (EMF) in natural ecosystems. However, this point remains mostly overlooked in managed ecosystems, especially in agriculture. Here, we compiled promising strategies for the targeted exploitation of the associations between microbial diversity and EMF of agricultural soils using samples from two long‐term (more than 30 years) experimental field sites in southern China. The two sites experienced a similar monsoon climate and fertilization management practices. We used high‐throughput amplicon sequencing, structural equation modelling and random forest analysis, to analyse our data and validate our hypotheses. We found that soil physiochemical properties and the C‐, N‐, P‐ and S‐cycle enzyme activities were increased with the increase in microbial diversity. Specifically, a positive linear relationship was observed between microbial diversity and EMF, which was mediated by long‐term fertilization management via changes in soil microbial communities and physiochemical properties. Random forest analysis and SEM showed that the important role of microbial diversity on EMF was maintained even when simultaneously taking multiple multifunctionality drivers (soil physiochemical properties, soil aggregation and enzymatic patterns) into account. In addition, microbial diversity, C‐cycle enzyme activity and pH value are feasible predictors of EMF; these factors were shown to be the main drivers of EMF of arable soils. Our findings suggest that there may be a limited degree of multifunctional redundancy in arable soils. The relationship we observed between microbial diversity and EMF suggests that management practices that foster more diverse soil microbial communities may have the potential to improve the functioning of agroecosystems. A plain language summary is available for this article. Abstract : Plain Language Summary